2016
DOI: 10.4236/jdm.2016.61003
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hyperglycemia, C-Reactive Protein and Other Risk Factors in Patients at Cardiovascular Risk

Abstract: Type 2 diabetes (DM2) is a syndrome characterized by postprandial hyperglycemia normally due to peripheral resistance to insulin and accounts for approximately 90% of diabetes cases worldwide and it is usually related to dyslipidemia, overweight/obesity and physical inactivity and increase in the risk of cardiovascular disease. This study aimed to compare the metabolic and inflammatory profile of hyperglycemic with non-hyperglycemic subjects in a group of patients undergoing coronary arteriography. Our group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…This protein has a common role with leptin in regulating fatty tissue mass and concentration of free fatty acids stored in it [34]. Induction of diabetes elevated CRP plasma levels, but this elevation was statically non-significant, while it was consistent with a previous study [35].…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This protein has a common role with leptin in regulating fatty tissue mass and concentration of free fatty acids stored in it [34]. Induction of diabetes elevated CRP plasma levels, but this elevation was statically non-significant, while it was consistent with a previous study [35].…”
Section: Resultssupporting
confidence: 79%
“…In this study, to evaluate the association of reduced endothelial dysfunction potential in diabetic wistars, which had been treated by fluoroquinolones, with reduced CRP plasma levels, the ratio of the increase in CRP in the four studied groups after the treatment with moxifloxacin, and levofloxacin, for sufficient time as antibiotics, according to the recommendations (14 days), was compared; CRP was re-evaluated after waiting for four months after post-treatment with fluoroquinolones; a comparison of CRP levels of non-diabetic group between the period pre-and post-fluoroqinolones treatment (i.e. a four-months interval) showed a statistically non-significant increase in CRP plasma levels, which is due to aging [37], while the increase in CRP plasma levels in the three diabetic groups within the same period was statistically significant; the increase in CRP plasma levels in the three diabetic groups was due to two factors: aging [37] and chronic hyperglycemia [35], plasma CRP levels in rats were less than 2 mg/L in all groups, which was consistent with some studies [38]. In addition, comparing the increased ratio among the four groups showed that there were a statistically significant increased ratio between diabetic groups and non-diabetic one, without a statistically significant difference among the three diabetic groups in CRP levels increasing ratio.…”
Section: Resultsmentioning
confidence: 85%
“…Our observations are consistent with in vitro studies carried out by Pasceri et al 29 , who point the direct involvement of CRP in the induction of adhesion molecules expression in human coronary artery endothelial cells. The study conducted by Barbalho et al 61 in the group of patients undergoing arteriography showed higher levels of lipids and CRP in patients with hyperglycemia compared to normoglycemic ones. It is believed that the accumulation of this protein in the subendothelial space depends both on its systemic concentration and local synthesis.…”
Section: Discussionmentioning
confidence: 91%